Acute Spontaneous Intracerebral Hemorrhage Management Update: Five New Things You Should Know - Justin Yu Hin Phung; Vignan Yogendrakumar; Dar Dowlatshahi (Annals of Indian Academy of Neurology)
Intracerebral hemorrhage (ICH) is a devastating condition responsible for millions of global deaths each year. Recent shifts in ICH management highlight a comprehensive care approach focusing on five pivotal components: prediction of hematoma expansion, blood pressure control, hemostasis, anticoagulation reversal, and surgical intervention. Radiological imaging allows clinicians to identify high-risk patients and implement approaches geared toward stabilizing hematoma volume to improve neurological outcomes. Surgical interventions and hematoma evacuation for cerebellar, intraventricular, and supratentorial ICH may also be used to reduce the mass effect from hematomas. This review will highlight the need to integrate all five strategies where appropriate into a bundle of care, with an emphasis on ongoing research in acute ICH management.